2021
DOI: 10.33910/2687-1270-2021-2-1-49-60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of impaired kynurenine synthesis on memory in Drosophila

Abstract: Опубликовано Российским государственным педагогическим университетом им. А. И. Герцена. Открытый доступ на условиях лицензии CC BY-NC 4.0.Аннотация. Проблема продолжительности жизни, особенностей медицинской помощи населению пожилого и старческого возраста становится все актуальнее в большинстве стран мира, в том числе и в России. С увеличением продолжительности жизни нейродегенеративные заболевания (НДЗ) выходят в развитых странах на ведущее место. Одна из причин возникновения нейродегенеративных изменений в … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In our study, cn 1 demonstrated normal 2D STM in CCSP up to day 21 of adult life, but both KP mutants had impaired 8D LTM. The lack of 8D LTM was also shown for 5-day-old v 1 with absence of kynurenines and intact 3-h STM [ 42 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, cn 1 demonstrated normal 2D STM in CCSP up to day 21 of adult life, but both KP mutants had impaired 8D LTM. The lack of 8D LTM was also shown for 5-day-old v 1 with absence of kynurenines and intact 3-h STM [ 42 ].…”
Section: Discussionmentioning
confidence: 95%
“…Our data also suggest different mechanisms for the Drosophila STM and LTM. In young flies, 8D LTM was absent in both KP mutants and v 1 , whereas 2D LTM was intact in v 1 and cn 1 , and 3-h STM was intact in all the studied strains [ 27 , 42 ]. LTM preservation up to day 8 seems to require robust memory mechanisms impaired to varying degrees in KP mutants.…”
Section: Discussionmentioning
confidence: 99%
“…In the first case, the control UAS > limk1"+" hybrid had bright eyes due to v[1] recessive allele, in contrast to UAS > limk1-KD hybrid with the wild type dark red eyes. The observed 3 h STM differences are unlikely to be associated with the differences in eyes pigmentation, as v[1] flies showed a normal 3 h STM and 2 day LTM in CCSP (Nikitina et al, 2021), while both forms of memory were impaired in the control strain. However, memory retention depends on parent affect, with some paternal epigenetic factors affecting STM strength (Medvedeva et al, 2021).…”
Section: генетика насекомых / Insect Geneticsmentioning
confidence: 99%